Parental Strategies of Indonesian Overseas Migrants in Preserving Their Child’s Bilingualism - Andi Syurganda (Journal of Research and Multidisciplinary, 2021)
Temporary or permanent overseas migration has been identified as one of a number of factors that lead Indonesian children to become bilingual or multilingual, among others, by Utomo (2014). The present study interviewed five Indonesian parents living temporarily in Australia and five parents who had returned to Indonesia to investigate the parental strategies they employed in their effort to maintain their children’s bilingualism. The qualitative data were analysed using thematic analysis, in relation to seven parental strategies for bilingual families identified by Barron-Hauwaert (2004), which were used as the theoretical framework for this study. The findings indicated that the current residents employed the ‘minority language at home’ (mL@H), trilingual/multilingual, and ‘one parent one language—majority language is strongest’ (OPOL ML) strategies, whereas the returnees employed the mL@H, ‘one parent one language—support for minority language’ (OPOL mL), and mixed strategies at home. The ML@H strategy (also called the ‘home outside the home’ strategy) was found to be the most used strategy by the Indonesian parents from both groups.